2009
DOI: 10.1128/jb.01342-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ColE1 MbeC Unveils an Extended Ribbon-Helix-Helix Family of Nicking Accessory Proteins

Abstract: MbeC is a 13-kDa ColE1-encoded protein required for efficient mobilization of ColE1, a plasmid widely used in cloning vector technology. MbeC protein was purified and used for in vitro DNA binding, which showed that it binds specifically double-stranded DNA (dsDNA) containing the ColE1 oriT. Amino acid sequence comparison and secondary structure prediction imply that MbeC is related to the ribbon-helix-helix (RHH) protein family. Alignment with RHH members pointed to a conserved arginine (R13 in MbeC) that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…The presence of the highly conserved structural motif LxxugxNlNQiaxxLn in the C- terminal part classifies MobC and its PromA homologs [4446], as the putative conjugative transfer auxiliary proteins of MOB P relaxases [13]. …”
Section: Resultsmentioning
confidence: 99%
“…The presence of the highly conserved structural motif LxxugxNlNQiaxxLn in the C- terminal part classifies MobC and its PromA homologs [4446], as the putative conjugative transfer auxiliary proteins of MOB P relaxases [13]. …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified a family of Dtr accessory factors with a common structural basis for oriT binding and relaxase recruitment. These factors possess a ribbon-helix-helix (RHH) DNA binding motif resembling that described previously for the Arc/ CopG/Mnt family of transcriptional regulators (36,268,291 (36,58,192,268,291,297,299). X-ray structures are now available for RHH domains of NikA and VirC2, and results of structurebased mutational analyses firmly establish the importance of the RHH domain in oriT binding as well as the recruitment of and nicking by the relaxase (179,291).…”
Section: Accessory Dtr Processing Factorsmentioning
confidence: 99%
“…The tra genes encode a relaxase, a mating pair formation (MPF) complex and a type IV coupling protein. The oriT is recognized by the relaxase, which binds and nicks the DNA at the nic site within the oriT (Varsaki et al, 2009). The relaxase together with one or several auxiliary proteins are termed the relaxosome (Pansegrau et al, 1990).…”
Section: Introductionmentioning
confidence: 99%